Patterns of relation and premorbid personality in late paraphrenia and depression - Fuchs, Thomas (Psychopathology, 1999)
38 patients with late paraphrenia and 38 with endogenous depression of late onset were compared regarding interpersonal relations and personality traits by means of semistructured interviews. The prevalence of premorbid personality disorder was determined by the Structured Clinical Interview for DSM-III-R Personality Disorders. The main objective of the study was to look for lifetime relation patterns and personality traits distinguishing the two groups and pointing to a specific premorbid vulnerability of paranoid and depressive patients. A high rate of personality disorder comorbidity was found in both groups, with mainly paranoid and schizoid disorder in late paraphrenic patients (39%) and avoidant, dependent or compulsive personality in depressives (35%). As a rule, this corresponded to a lifelong pattern of seclusion and self-sufficiency in the paranoid, and of close intimacy and heteronomy in the depressive patients. On the basis of the results, a polar typology of personality and interpersonal relations in both patient groups is developed.